Mutation of a C-Terminal Motif Affects Kaposi's Sarcoma-Associated Herpesvirus ORF57 RNA Binding, Nuclear Trafficking, and Multimerization - Taylor, Adam (American Society for Microbiology, 2011)
The Kaposi's sarcoma-associated herpesvirus (KSHV) ORF57 protein is essential for virus lytic replication. ORF57 regulates virus gene expression at multiple levels, enhancing transcription, stability, nuclear export, and translation of viral transcripts. To enhance the nuclear export of viral intronless transcripts, ORF57 (i) binds viral intronless mRNAs, (ii) shuttles between the nucleus, nucleolus, and the cytoplasm, and (iii) interacts with multiple cellular nuclear export proteins to access the TAP-mediated nuclear export pathway. We investigated the implications on the subcellular trafficking, cellular nuclear export factor recruitment, and ultimately nuclear mRNA export of an ORF57 protein unable to bind RNA. We observed that mutation of a carboxy-terminal RGG motif, which prevents RNA binding, affects the subcellular localization and nuclear trafficking of the ORF57 protein, suggesting that it forms subnuclear aggregates. Further analysis of the mutant shows that although it still retains the ability to interact with cellular nuclear export proteins, it is unable to export viral intronless mRNAs from the nucleus. Moreover, computational molecular modeling and biochemical studies suggest that, unlike the wild-type protein, this mutant is unable to self-associate. Therefore, these results suggest the mutation of a carboxy-terminal RGG motif affects ORF57 RNA binding, nuclear trafficking, and multimerization.